Assessing the Transferability of Highway Safety Manual Predictive Method for Urban Roads in Fortaleza City/Brazil - Flávio Cunto (2013)
The Highway Safety Manual (HSM) provides guidance to safety professionals becoming a standard of practice, particularly for regions where acting is urgent as a result of an overall lack of safety investments leading to persistently high crash frequencies. Differences in crash data systems, local enforcement, driving behavior, and other factors have fostered researches focused on assessing the international transferability of the HSM predictive method. The recent increase in crash occurrences in Brazilian urban areas and the decade of action for road safety WHO initiative has motivated a nationwide joint safety research effort. One of the fundamental questions in this project is related to the applicability of HSM safety performance functions (SPFs) for the Brazilian urban environment. This paper presents the initial results regarding the transferability of HSM SPFs for estimating expected average crash frequency of urban intersections in Fortaleza City. The procedure applied comprehended two major steps: the first step was focused on the estimation of the calibration factor according the procedure outlined in the HSM, followed by a subsequent model validation effort using a different sample; the second step comprised an analysis of the overdispersion parameter k, either using the original estimates from the HSM or recalibrated estimates using local conditions. The results suggested that for the Fortaleza case, calibrated HSM baseline SPFs can be applied with caution. It is however, worthwhile analyzing the effect of the calibration sample